2022
DOI: 10.1186/s12940-021-00811-1
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic exposure during pregnancy and postpartum maternal glucose tolerance: evidence from Bangladesh

Abstract: Background Arsenic exposure has been associated with gestational diabetes mellitus. However, the extent to which arsenic exposure during pregnancy is associated with postpartum glucose intolerance is unknown. Methods We studied 323 women in Bangladesh. We assessed arsenic exposure in early pregnancy via toenail and water samples. We measured fasting glucose and insulin in serum at a mean (SD) of 4.0 (3.5) weeks post-delivery. We ran covariate-adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The burden of cardiovascular disease attributable to arsenic in drinking water significantly impacts young and healthy women [ 38 , 39 , 83 ]. In a Bangladesh cohort, there was no clear evidence for an effect of arsenic exposure during pregnancy, on postpartum insulin resistance or beta cell function, in contrast to what has been described in the literature [ 84 ].…”
Section: Reviewmentioning
confidence: 99%
“…The burden of cardiovascular disease attributable to arsenic in drinking water significantly impacts young and healthy women [ 38 , 39 , 83 ]. In a Bangladesh cohort, there was no clear evidence for an effect of arsenic exposure during pregnancy, on postpartum insulin resistance or beta cell function, in contrast to what has been described in the literature [ 84 ].…”
Section: Reviewmentioning
confidence: 99%
“…Ten additional studies were also evaluated but did not fulfil the inclusion criteria and were accordingly not considered further (Fleisch et al, 2022 ; Lampron‐Goulet et al, 2017 ; Mondal et al, 2020 ; Ourshalimian et al, 2019 ; Park et al, 2016 ; Paul et al, 2019 ; Su et al, 2012 ; Tinkelman et al, 2020 ; Wang, Mukherjee, et al, 2020 ; Zhou, Zhao, & Huang, 2022 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Although arsenic (As) has been reported to be one of the environmental factors contributing to the increased risk of GDM, information on the relationship between arsenic species and GDM is very limited. Determining the concentrations of arsenic species in the biospecimen is vital because the toxicity of arsenic species varies greatly. A small number of epidemiologic studies with varied assessment designs and methods have shown inconsistent results. The effect of specific arsenic species on GDM is not well understood.…”
Section: Introductionmentioning
confidence: 99%